Pengaruh Thin Capitalization, Revaluasi Aset Tetap dan Profitabilitas Terhadap Penghindaran Pajak : Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdapat di Bei Periode 2019 – 2022 - Ayu Susanti; Agrianti Komalasari (Jurnal Riset Akuntansi, 2025)
This study aims to analyze the effect of thin capitalization, fixed asset revaluation, and profitability on tax avoidance in property and real estate companies listed in Indonesia Stock Exchange (IDX) for the period 2019-2022. This study employs a quantitative method using secondary data obtained from financial reports of companies that meet the purposive sampling criteria. Multiple linear regression analysis is used to examine the relationship between independent and dependent variables. The findings indicate that thin capitalization, fixed asset revaluation, and profitability have a positive and significant effect on tax avoidance. This suggests that higher debt utilization, fixed asset revaluation, and profitability increase the likelihood of companies engaging in tax avoidance practices. These findings are expected to provide insights for stakeholders, including the government, investors, and academics, in understanding tax avoidance practices and formulating more effective policies to mitigate potential revenue losses due to such practices.